Elevated sweat chloride test: is it always cystic fibrosis? - C. Cimbalo; A. Tosco; V. Terlizzi; A. Sepe; A. Castaldo; L. Salvadori; V. Raia (BMC, 2021)
Abstract Background The sweat chloride test (ST) is the gold standard for cystic fibrosis (CF) diagnosis in symptomatic patients, within the newborn screening and in the follow-up of CF patients during molecular therapies. However, false positives have been reported in patients with different diseases. We describe and discuss 4 cases due to different clinical conditions in which we recorded false positive ST, and the test remained altered for a period of varying length. Cases presentation Case 1: Eight months old female child suffering from constipation, recurrent vomiting and failure to thrive, family history of recurrent pancreatitis without mutations in the PRSS1 and SPINK1 genes. Both ST and fecal elastase were altered although no CFTR gene mutations were found. Due to rapid clinical deterioration, celiac disease was suspected and diagnosed by laboratory tests and intestinal biopsy. After 2 weeks of gluten-free diet ST and fecal elastase normalized. Case 2: 14 months old male suffering from bilateral renal dysplasia, episodes of metabolic alkalosis, recurrent respiratory infections and recurrent vomiting. The child had more ST positives, but no CFTR mutations were found. During follow-up, he developed sensorineural hearing loss and an atrial septic defect was found. Finally, a diagnosis of Klinefelter was made, but the ST normalized several years later. Case 3 and 4: Two boys with stubborn constipation and fecal occlusion treated with Poly Ethylene Glycol (PEG) with salts showed pathological ST. The test returned normal a few days after stopping treatment. Conclusions We hypotesized the possible causes of ST alteration in these conditions: in celiac disease it could be due to a transient dysregulation of the aquaporins, rapidly reversed by the diet; in Klinefelter, it may be due to stable pubertal hypoandrogenism; while, the PEG formulation itself contains salts that can temporarily alter ST.